Nilai-nilai Pendidikan Islam dalam Karya Seni Kaligrafi - Sari, Dwi Nur Indah; Khoirunnisa, Jany Fitria; Hafidhdin, Muhammad; Anshori, Aries Anang; Ichsan, Yazida (Al-DYAS, 2023)
Calligraphy is the art of writing the Qur'an using certain techniques so that it has aesthetic value. Writing calligraphy is not only used as a skill. But there are values of Islamic education contained in it. Because basically the purpose of Islamic education is to make students have noble character and be able to maximize their role as servants of Allah and caliphs on earth. Even the first revelation of Allah SWT that came down was an order to read and write. This is the basis for the author to conduct this research. In this study the authors used qualitative research methods with literature study data collection techniques. This study aims to determine the values of Islamic education contained in calligraphy artwork. From various scientific sources, it is proven that in writing calligraphy there are Islamic educational values contained in it, namely education on aqidah, morals, and worship.